Alterations in the proteome of pulmonary alveolar type II cells in the rat after hepatic ischemia-reperfusion - Hirsch, Jan (2008)
OBJECTIVE: Hepatic ischemia-reperfusion can be associated with acute lung injury. Alveolar epithelial type II cells (ATII) play an important role in maintaining lung homeostasis in acute lung injury. DESIGN: To study potentially new mechanisms of hepatic ischemia-reperfusion-induced lung injury, we examined how liver ischemia-reperfusion altered the proteome of ATII. SETTING: Laboratory investigation. SUBJECTS: Spontaneously breathing male Zucker rats. INTERVENTIONS: Rats were anesthetized with isoflurane. The vascular supply to the left and medial lobe of the liver was clamped for 75 mins and then reperfused. Sham-operated rats were used as controls. After 8 hrs, rats were killed. MEASUREMENTS AND MAIN RESULTS: Bronchoalveolar lavage and differential cell counts were performed, and tumor necrosis factor-α and cytokine-induced neutrophil chemotactic factor-1 in plasma were determined by enzyme-linked immunosorbent assay. ATII were isolated, lysed, tryptically digested, and labeled using isobaric tags (iTRAQ). The samples were fractionated by cation exchange chromatography, separated by high-performance liquid-chromatography, and identified using electrospray tandem mass spectrometry. Spectra were interrogated and quantified using ProteinProspector. Quantitative proteomics provided quantitative data for 94 and 97 proteins in the two groups. Significant changes in ATII protein content included 30% to 40% increases in adenosine triphosphate synthases, adenosine triphosphate/adenosine diphosphate translocase, and catalase (all p < .001). Following liver ischemia-reperfusion, there was also a significant increase in the percentage of neutrophils in bronchoalveolar lavage (48% ± 26%) compared with sham-operated controls (5% ± 3%) (p < .01), and plasma tumor necrosis factor-α levels were also significantly increased. CONCLUSIONS: The proteins identified by quantitative proteomics indicated significant changes in moderators of cell metabolism and host defense in ATII. These findings provide new insights into possible mechanisms responsible for hepatic ischemia-reperfusion-related acute lung injury and suggest that ATII cells in the lung sense and respond to hepatic injury.